Voskresen'e . Voskresen'e . Sunday . Воскресенье - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The 83rd anniversary of the death of Lev Tolstoy and Boris Yeltsin's visit to the house-museum IAsnaia Poliana; preparations for the elections to the Federal Assembly of the Russian Federation; private land ownership; the military doctrine of the Russian Federation; introduction of the regime of special regime of residence in Moscow; the rise of food prices; the cessation of supplies of Kazakh oil to the Saratov Petroleum plant; financial crisis in Tajikistan; refugees on the territory of the Commonwealth of Independent States; exhibition "From Manet to Picasso" in the State Museum of Fine Arts named after Aleksandr Pushkin. Featured in the program: Yeltsin, Boris Nikolayevich (President of the Russian Federation); Chubais, Anatolii Borisovich (Chairman of the Committee for Managing State Property of the Russian Federation) Contributors: Alekseev, Sergei (Anchor) 83я годовщина смерти Льва Толстого и посещение дома-музея в Ясной Поляны Борисом Ельциным; подготовка к выборам в Федеральное Собрание Российской Федерации; сюжет частное землевладение; военная доктрина Российской Федерации; введение особого режима проживания в Москве; рост цен на продукты питания; прекращение поставок казахской нефти на Саратовский нефтеперерабатывающий завод; финансовый кризисе в Таджикистане; беженцы на территории Содружества Независимых Государств; выставка "От Мане до Пикассо в Государственном Музее Изобразительного Искусства им. А. С. Пушкина. В программе участвуют: Ельцин, Борис Николаевич (Президент Российской Федерации); Чубайс, Анатолий Борисович (Председатель комитета по управлению государственным имуществом Российской Федерации) Создатели: Алексеев, Сергей (Ведущий/Ведущая)